Health Monitoring System Using Classification Algorithm in Big Data - Gladiss Merlin N.R, Dr.Vigilson Prem M (International Journal of Control and Automation, 2020)
Health has prime significance in our everyday life. Because of the absence of wellbeing checking, understanding experiences genuine medical problems. Internet of Things is the cutting edge innovation valuable for the clinical wellbeing segment in numerous ways. In this venture we structure human services checking framework utilizing Temperature and Heart beat sensors which detects understanding heartbeat rate and internal heat level and cautions the wellbeing experts through a SMS, if the readings falls past basic Values. This framework will likewise be associated with the TS Cloud for the information perception for assistance the Esp8266 WiFi module so tolerant wellbeing can be observed from anyplace in the world. The gathered information is additionally handled by applying different information mining calculations like Naive Bayes, Random Forest tree and SVM to separate concealed examples. We present the outcomes acquired from the handling of calculations dependent on exactness, accuracy and order time.